EFEK INTENSITAS CAHAYA RENDAH TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS KEDELAI LOKAL ACEH - Taufan Hidayat (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2021)
This study aims to determine the effect of Aceh soybean and national varieties to different levels of light intensity. The soybean varieties were used two Aceh soybean varieties (Bener Meriah and Kipas Merah varieties) and two national varieties (Anjasmoro and Dering varieties). The percentage of light intensity tested includes a light intensity of 40%, 60%, 80% and 100%. The study was conducted using a split plot design with three replications. The parameters were including plant height, seed weight of 100 grains and results, as well as the microclimate observations included temperature and humidity. The results showed that the best soybean growth rate obtained on the level of light intensity of 40%. As for the treatment of soybean varieties, in fact showed a growth rate of Bener Meriah varieties, Dering and Anjasmoro better than Kipas Merah. On production parameters, varieties of Bener Meriah and Dering showed better productivity levels than Kipas Merah and Anjasmoro.